Nove oblike bivanja - trajnostno usmerjene urbane skupnosti - Šašek-Divjak, Mojca (Urbani izziv, 2000)
Various new forms of settlements composed of sustainable communities are emerging all around the World as answers to the urban crises in great cities. These settlements differ, especially when comparing the countries the countries where they appear. However they also have many common features, such as the humane scale and social community cohesion, public participation in their management, enforcing new societal values and sustainable orientation of activities. These settlements where developed following development of information and communication technology and correspond to the introduction of new styles of life and employment.
Keywords: ecology; ekologija; mesta; sonaravni razvoj; sustainable development; trajnostni razvoj; urbana naselja; urbanism; urbanizem